2007
DOI: 10.1093/eurheartj/ehm051
|View full text |Cite
|
Sign up to set email alerts
|

Release of cardiac bio-markers during high mechanical index contrast-enhanced echocardiography in humans

Abstract: Our data suggest that high-MI contrast-enhanced echocardiography can cause subclinical release of cardiac bio-markers in humans, while low-MI real-time imaging appears to be safer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 27 publications
2
24
0
3
Order By: Relevance
“…These values are comparable to those found in other studies (Chen et al 2002;Vancraeynest et al 2007). cTnI is a highly specific and sensitive marker for myocardial damage, because it is not expressed in skeletal muscle and is not present in the blood circulation of healthy animals (O'Brien et al 2006;O'Brien 2008).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These values are comparable to those found in other studies (Chen et al 2002;Vancraeynest et al 2007). cTnI is a highly specific and sensitive marker for myocardial damage, because it is not expressed in skeletal muscle and is not present in the blood circulation of healthy animals (O'Brien et al 2006;O'Brien 2008).…”
Section: Discussionsupporting
confidence: 92%
“…However, it has been shown that the destruction of microbubbles with high-intensity ultrasound can cause bio-effects in small animals (Miller 2007) and induce mild troponin release and premature ventricular contractions in humans (van der Wouw et al 2000;Vancraeynest et al 2007). To some extent, these bio-effects may open opportunities for therapeutic applications (Hernot and Klibanov 2008).…”
Section: Introductionmentioning
confidence: 99%
“…51, No. 12, 2008 Weyman March 25, 2008March 25, :1221 Year in Echocardiography stable patients with largely normal LV function but could not exclude the possibility that microscale myocyte damage might contribute to serious complications in hemodynamically unstable patients or those with ongoing myocardial infarction or ischemia (20). In interpreting these data it is important to note that the use of a 15-min continuous infusion, prolonged high MI imaging, and a single constant examining plane represent significantly more exposure than would occur in normal clinical practice.…”
Section: Mcementioning
confidence: 99%
“…This "petechiae bioeffect" phenomenon has also raised concerns about the clinical safety of contrast ultrasound. [22][23][24][25] The creation of petechiae bioeffects is dependent on ultrasound power [18][19][20]22,24 and pulsing interval. 26 Modeling studies predict that increasing peak-negative acoustic pressure from 0.2 to 0.5 MPa increases the level of microvessel wall stress caused by MB expansion by 2 orders of magnitude, to a value above the critical threshold for vessel rupturing.…”
mentioning
confidence: 99%